Clinical evidence of immunogenicity of CAR-T cell therapies and its implication in the clinical development of CAR-T drug products - Hammodah R. Alfar; Hammodah R. Alfar; Cecil Chen; Eric Lachacz; Weifeng Tang; Yuqian Zhang (Frontiers in Immunology)
Chimeric antigen receptor-engineered T cell therapies (CAR-T) are becoming powerful immunotherapeutic tools for treating malignancies, especially hematological malignancies. Like other biological drugs, CAR-T cell products can trigger unwanted immune responses in patients receiving the treatment. This might lead to treatment failure or life-threatening consequences. This immunogenicity could also affect the CAR-T cells’ cellular kinetics and clinical responses. In this review, we summarize the immunogenicity of biologics and their effects on PK/PD profiles, safety, and efficacy. We also introduce the mechanisms of immunogenicity induced by CAR-T cells and clinical evidence of immunogenicity of the currently FDA-approved CAR-T cell products. Particularly, we summarize the currently available immunogenicity data from each CAR-T cell product’s clinical trials, immunogenicity assays, sample types, and preclinical efficacy models, which were retrieved from the FDA and EMA websites. We also discuss a preclinical model that is promising for evaluating CAR-T cell immunogenicity.